2023
DOI: 10.1111/nin.12569
|View full text |Cite
|
Sign up to set email alerts
|

Increasing a patient's sense of security in the hospital: A theory of trust and nursing action

Abstract: Having a decreased sense of security leads to unnecessary suffering and distress for patients. Establishing trust is critical for nurses to promote a patient's sense of security, consistent with trauma‐informed care. Research regarding nursing action, trust, and sense of security is wide‐ranging but fragmented. We used theory synthesis to organize the disparate existing knowledge into a testable middle‐range theory encompassing these concepts in hospitals. The resulting model illustrates how individuals are ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…For example, caring interactions require nurses to demonstrate unique perspectives they have of their patients, creating opportunities to want to get to know them while providing a sense of security and comfort in the patient's care setting. To convey this sense, nurses need to use strategies that create an atmosphere to help patients 'open up' and share their thoughts, feelings, and concerns [6,7] . It is suggested that such sharing has the potential for patients to feel their own worth through reaffirming their intrinsic value [7] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, caring interactions require nurses to demonstrate unique perspectives they have of their patients, creating opportunities to want to get to know them while providing a sense of security and comfort in the patient's care setting. To convey this sense, nurses need to use strategies that create an atmosphere to help patients 'open up' and share their thoughts, feelings, and concerns [6,7] . It is suggested that such sharing has the potential for patients to feel their own worth through reaffirming their intrinsic value [7] .…”
Section: Introductionmentioning
confidence: 99%